2004
DOI: 10.1002/pssb.200304263
|View full text |Cite
|
Sign up to set email alerts
|

CdSe‐based nanostructures: growth, properties, lasers

Abstract: Paper presents an overview of recent results on novel CdSe quantum dot (QD) fabrication techniques with the main impact on a stressor-controlled self-organization process resulting in nucleation of real CdSe QDs optically active up to room temperature, with a narrower size distribution, a higher density and a high Cd content. The main idea of the stressor-controlled epitaxy is an intentional introduction of a superstrained fractional monolayer of the much higher lattice-mismatch compound -stressor -to create s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previously [6], we performed a kinematical Monte-Carlo simulation of the CdSe QD growth initiated by deposition of ultra-thin CdTe layer in a BeTe matrix. We have shown that …”
Section: Discussionmentioning
confidence: 99%
“…Previously [6], we performed a kinematical Monte-Carlo simulation of the CdSe QD growth initiated by deposition of ultra-thin CdTe layer in a BeTe matrix. We have shown that …”
Section: Discussionmentioning
confidence: 99%